(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Total Physical Response has many benefits on the part of the learner. One of them is being characterized by simplicity since the verb forms used for commands are in simple form. Another one is long-term retention; the constant repetition makes language memorable and makes students remember almost everything they learn. Besides, TPR decreases stress and makes EFL learners come across relaxed and pleasing experiences. It also increases students’ motivation during lessons thanks to its high rate of success. More than that, TPR makes learners interested in learning English as a foreign language as it is funny and students enjoy it and it makes them full of energy and enthusiasm. This is besides the fact that it takes into account two learning styles: the auditory and the kinesthetic Learning. This theory also has many benefits on the part of the teacher. In this respect, simple TPR activities do not require neither a great deal of preparation, nor expensive or demanding materials. So, as long as the teacher is competent, just an easy rehearsal beforehand can help. Concerning the formative assessment of students, teachers will know immediately whether or not students understood what was taught.